A study on state policies/discourses in affecting the ways in which women of the baby boomers generation in Singapore deal with ageing - Tan, Xiwen (2015)
Abstract: Ageing population is a significant demographic challenge that Singapore is expected to face in the near future. This research explores the views of women of the Baby Boomers Generation in Singapore, focusing on how state policies and discourses have affected the ways in which these women view the process of ageing, illness and death. Qualitative interviews were conducted with 10 women of a similar socioeconomic status, to find out their envisioned retirement life. Also, it explores ways in which state discourses of filial piety, and policies targeted at encouraging individuals to be responsible instead of relying on state welfare have shaped these women’s views towards their retirement life.